Deteksi Asam Mefenamat pada Jamu Pegel Linu yang beredar di Wilayah Pekalongan - Rusmalina, Siska; Khasanah, Kharismatul; Nugroho, Denny Kurniawan (Pharmacon: Jurnal Farmasi Indonesia)
Jamu Pegel Linu is one of the most popular herbs in Indonesia and oftenly the producers added medicinal chemicals (BKO) so that the resulting therapeutic effect is more effective. One of the BKO added is mefenamic acid. The added content of mefenamic acid can cause harmful side effects such as seizures and can even cause coma. This study aimed to detect the BKO content of mefenamic acid in Jamu Pegel Linu distributed in Pekalongan region. This research was a descriptive study with purposive sampling. The sample used was all Jamu pegel linu that were distributing in Pekalongan region that were included the inclusion and exclusion criteria. The analytical method used is Thin Layer Chromatography (TLC) with a mobile phase in the form of ethyl acetate: methanol: ammonia (80:10:10). Spotting detection was carried out under UV light at Î» 254 nm. The results of the spots obtained were compared with a comparison standard. To ensure the results obtained are confirmed using the color reaction method. The results of testing of 27 samples by TLC method obtained there are 3 (three) samples of herbal medicine giving positive results indicated by the similarity of rf values with comparative standards. The results obtained were tested qualitatively with color reagents to strengthen the results.